SOCIOLINGUISTIC ANALYSIS OF JARGON USED IN EXTRACURRICULAR ORGANIZATION OF UNIVERSITAS ISLAM MADURA - Budin, Wahi; YB, Dinar Vincy (Jurnal JOEPALLT (Journal of English Pedagogy, Linguistics, Literature, and Teaching), 2022)
Sociolinguistics is an interdisciplinary study of linguistics that relates language as an object of study to the social order of society. To analyze sociolinguistics, linguistic theory can be used. In this study, researcher found various types of jargon. The jargons are varied, some are in the form of words, phrases, and abbreviations. The word is the word is the smallest language unit that fills one of the syntactic functions (subject, predicate, object, or description) in a sentence. The jargon in the form of phrases found generally consists of two or more words. In addition, there is also a lot of jargon in the form of abbreviation. acronyms and short are part of abbreviation. In this study, the objects analyzed are sentences that are often thrown out during official activities or during leisure time. The researcher used qualitative research methods in conducting this research because the one who obtained the data was the only research source. In addition, this is a descriptive study because the researcher represents the findings descriptively. The results of this study are sociolinguistic analysis on three extracurricular organizations at the Islamic University of Madura using three approaches, observation, interview, and documentation. In this study, researcher found several patterns of jargon. The results of this study, researcher found 23 jargon in the three organizations. There are three types of jargon patterns. Based on the results of this study, the researcher hopes that the research can become significant data for the linguistic community and a starting point for future researcher, especially those who are interested in studying sociolinguistics. This research is expected to increase the reader's knowledge about jargon and its relationship in society.